2021
DOI: 10.3847/1538-4357/abf0a0
|View full text |Cite
|
Sign up to set email alerts
|

The Cosmic Ultraviolet Baryon Survey (CUBS). II. Discovery of an H2-bearing DLA in the Vicinity of an Early-type Galaxy at z = 0.576*

Abstract: We report the serendipitous detection of an H2-bearing damped Lyα absorber at z = 0.576 in the spectrum of the QSO J0111–0316 in the Cosmic Ultraviolet Baryon Survey. Spectroscopic observations from Hubble Space Telescope-COS in the far-ultraviolet reveal a damped absorber with log[N(H i)/cm−2] = 20.1 ± 0.2 and log[N(H2)/cm−2] . The diffuse molecular gas is found in two velocity components separated by Δ ν ≈ 60 km s−1, with >… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that the CGM is multiphase, including cold molecular gas, cool photoionized gas, warm-hot collisionallyionized gas, and hot X-ray/𝛾-ray emitting plasma (e.g., Savage et al 2014;Werk et al 2016;Bogdán et al 2017;Li et al 2018;Das et al 2020;Boettcher et al 2021;Karwin et al 2021). Theoretically, the volume-filling hot medium is formed via virial shocks and galactic feedback (e.g., Cen & Ostriker 2006), while lower temperature gas is confined within this volume-filling hot medium in the forms of clouds or filaments.…”
Section: The Prevalence Of Multiphase Gas At 𝒅 < 100 Kpcmentioning
confidence: 99%
“…Previous studies have shown that the CGM is multiphase, including cold molecular gas, cool photoionized gas, warm-hot collisionallyionized gas, and hot X-ray/𝛾-ray emitting plasma (e.g., Savage et al 2014;Werk et al 2016;Bogdán et al 2017;Li et al 2018;Das et al 2020;Boettcher et al 2021;Karwin et al 2021). Theoretically, the volume-filling hot medium is formed via virial shocks and galactic feedback (e.g., Cen & Ostriker 2006), while lower temperature gas is confined within this volume-filling hot medium in the forms of clouds or filaments.…”
Section: The Prevalence Of Multiphase Gas At 𝒅 < 100 Kpcmentioning
confidence: 99%
“…Despite the availability of large samples of intervening DLAs (e.g., Noterdaeme et al 2009;Parks et al 2018) and the fact that they trace the bulk of neutral hydrogen in the Universe (Wolfe et al 2005), the detected DLAs show little dust (e.g. Murphy & Liske 2004) and only a small fraction exhibit the presence of molecular hydrogen (Petitjean et al 2000;Ledoux et al 2003;Noterdaeme et al 2008;Srianand et al 2012;Noterdaeme et al 2015;Muzahid et al 2015;Balashev & Noterdaeme 2018;Zahedy et al 2020;Boettcher et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We refer the reader to Chen et al (2020) for a description of the absorption-line observations of J2339-5523 from the Cosmic Origins Spectrograph (COS) on HST (𝜆 = 1100-1800 Å, spectral resolution FWHM ≈ 20 km s −1 ) and the Magellan Inamori Kyocera Echelle (MIKE) spectrograph on Magellan-Clay (𝜆 = 3200-9200 Å, FWHM ≈ 8 km s −1 ). We use Voigt profile fitting to determine the velocity (𝑣), Doppler parameter (𝑏), and column density (𝑁) of the atomic and ionic transitions associated with the DLA using a grid search as described in §3 of Boettcher et al (2021). The COS wavelength calibration is sufficiently uncertain that we allow small variations within 𝛿𝑣 = ±5 km s −1 for low and intermediate ions in COS with respect to Ca II𝜆𝜆3934, 3969 in MIKE.…”
Section: Uv Absorption-line Analysismentioning
confidence: 99%